2014
DOI: 10.18632/aging.100664
|View full text |Cite
|
Sign up to set email alerts
|

Short leukocyte telomere length is associated with obesity in American Indians: The strong heart family study

Abstract: Shorter leukocyte telomere length (LTL) has been associated with a wide range of age-related disorders including cardiovascular disease (CVD) and diabetes. Obesity is an important risk factor for CVD and diabetes. The association of LTL with obesity is not well understood. This study for the first time examines the association of LTL with obesity indices including body mass index, waist circumference, percent body fat, waist-to-hip ratio, and waist-to-height ratio in 3,256 American Indians (14-93 years old, 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
54
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 43 publications
3
54
1
Order By: Relevance
“…Thus, genetic factors [16] and the intrauterine environment [17][18][19] might play a role in fashioning TL, which, in turn, may have a major impact on the risk of metabolic diseases in adulthood. A recent clinical study in American Indians showed that short LTL was associated with the incidence of type 2 diabetes mellitus [20] and obesity [21]. The authors hypothesised that LTL could be used as a predictive marker of diabetes development in American Indians.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, genetic factors [16] and the intrauterine environment [17][18][19] might play a role in fashioning TL, which, in turn, may have a major impact on the risk of metabolic diseases in adulthood. A recent clinical study in American Indians showed that short LTL was associated with the incidence of type 2 diabetes mellitus [20] and obesity [21]. The authors hypothesised that LTL could be used as a predictive marker of diabetes development in American Indians.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, several traditional and newly emerging risk factors are associated with CHD risk, 6,7 some of which, such as glycemic traits, lipids, and obesity, are also closely related to telomere shortening. [8][9][10][11] Thus, these may act as potential mediators that lie in the pathway from telomere shortening to increased risk of CHD.…”
mentioning
confidence: 99%
“…Obesity is associated with significantly shortened leukocyte telomere length even when controlling for covariates such as age, smoking, C-reactive protein (CRP), diabetes, and hypertension [41]. Severely obese patients demonstrated shorter relative telomere length at baseline and one year after bariatric surgery, irrespective of whether they also had metabolic syndrome [42].…”
Section: Telomere Length and Dynamics In Somatic Diseasesmentioning
confidence: 99%